Targeting of IL-2 to cytotoxic lymphocytes as an improved method of cytokine-driven immunotherapy. (1st February 2017) - Lazear, Eric; Ghasemi, Reza; Hein, Sarah M.; Westwick, John; Watkins, Dan; Fremont, Daved H.; Krupnick, Alexander Sasha
ABSTRACT: The use of high-dose interleukin-2 (IL-2) has fallen out of favor due to severe life-threatening side effects. We have recently described a unique way of directly targeting IL-2 to cytotoxic lymphocytes using a virally encoded immune evasion protein and an IL-2 mutant that avoids off-target side effects such as activation of regulatory T cells and vascular endothelium.